Socioeconomic Impact of the Covid-19 Pandemic on Employment - Zuzana STOLIČNÁ; Loretta PINKE (Communications of International Proceedings, 2022)
The work environment has gone through a lot of changes, especially after the COVID-19 pandemics. The aim of this work is to focus on its impact in a globalized world from socio-economic perspective, where not just several factors will be compared but also quarterly data of different countries. The benefit of this work is to refer the consequences of the pandemic COVID-19.
Keywords: pandemics; economy; employment; unemployment.